Manajemen Nutrisi: Variasi Makan dan Pemberian Madu Temulawak Terhadap Ketidakseimbangan Nutrisi: Kurang dari Kebutuhan Tubuh pada Anak Demam Tifoid. - Candra Nurhidayati; Tutik Rahayuningsih (Jurnal Indonesia Sehat, 2023)
Background: Typhoid is an acute infectious disease that attacks the digestive system caused by the bacterium Salmonella typhosa. Imbalanced nutrition less than body requirements is one of the problems experienced by typhoid sufferers. To overcome this problem, the action of giving a variety of foods and temulawak honey can be carried out to increase appetite so that nutritional needs can be fulfilled. Purpose: to describe the nursing management of giving a variety of foods and temulawak honey for nursing problems of nutritional imbalances less than body requirements. Qualitative research methods use case studies with a nursing process approach. Population of typhoid children with nutritional imbalance: less than body requirements in Jonggolan village, non-probability sampling technique with purposive sampling method, three respondents as research subjects. Results: the study of three subject mothers said the child had no appetite, ate 2-3 tablespoons, dirty tongue, dry lip mucosa, nutritional imbalance nursing problems less than body requirements related to insufficient dietary intake. Nursing actions: examine food patterns, examine factors that cause nausea and vomiting, monitor body weight, provide a variety of foods, regulate diet: ginger honey supplement, after taking action for 14 x 24 hours the problem of nutritional imbalance is resolved, because the three subjects experience an increase in appetite, there is two subjects experienced weight gain and one subject did not increase. Conclusion: the management of giving a variety of foods and temulawak honey is effective in overcoming the problem of nutritional imbalances less than the body's needs.